2020
DOI: 10.1101/2020.04.23.051300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Gray Mold Infection in Plants Using a Multispectral Imaging System

Abstract: Gray mold disease caused by the fungus Botrytis cinerea damages many crop hosts worldwide 9and is responsible for heavy economic losses. Early diagnosis and detection of the disease would allow 10 for more effective crop management practices to prevent outbreaks in field or greenhouse settings. 11Furthermore, having a simple, non-invasive way to quantify the extent of gray mold disease is important 12for plant pathologists interested in quantifying infection rates. In this paper, we design and build a 13 multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Generally, the early detection of the B. cinerea infection in horticultural crops using nondestructive methods is an emerging topic. Such an evaluation method requires considering the relative position between the leaf and detector and the lighting conditions [3]. The study of Wu et al [24] showed 85% accuracy before infection symptoms were visible in eggplant leaves when the hyperspectral visible near-infrared (VNIR) spectroradiometer to measure reflectance intensities of healthy and B. cinerea inoculated plants was used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, the early detection of the B. cinerea infection in horticultural crops using nondestructive methods is an emerging topic. Such an evaluation method requires considering the relative position between the leaf and detector and the lighting conditions [3]. The study of Wu et al [24] showed 85% accuracy before infection symptoms were visible in eggplant leaves when the hyperspectral visible near-infrared (VNIR) spectroradiometer to measure reflectance intensities of healthy and B. cinerea inoculated plants was used.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the 552 nm and 701 nm wavelengths for detecting discolouration in lettuce leaves with over 99% accuracy were approved, but not for Botrytis fungal infection [25]. Scarboro et al demonstrated a process for selecting optimal spectral bands integrated into a two-band multispectral (540 and 670 nm) camera imaging system and evaluating its performance for detecting B. cinerea infection on lettuce leaves to monitor disease progression producing a true positive rate of 95.25% with a false positive rate of 9.316% [3]. Such findings, as mentioned earlier, can be considered for choosing leaf spectral reflectance indices according to the wavelengths used in the formulas of their calculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations